Dynamic Immune Function Changes Before and After the First Radioactive Iodine Therapy After Total Resection of Differentiated Thyroid Carcinoma - Shi, Zhi-Yong; Zhang, Sheng-Xiao; Fan, Di; Li, Cai-Hong; Cheng, Zhe-Hao; Xue, Yan; Wu, Li-Xiang; Lu, Ke-Yi; Yang, Su-Yun; Cheng, Yan; Wu, Zhi-Fang; Gao, Chong; et al. (Frontiers in Immunology, 2022)
Abstract The effects of total thyroidectomy or radioactive iodine therapy on immune activation and suppression of the tumor microenvironment remain unknown. We aimed to investigate the effects of these treatments on the immune function in patients with differentiated thyroid carcinoma (DTC). Our cohort included 45 patients with DTC treated with total thyroidectomy and radioactive iodine therapy (RAIT). Immune function tests were performed by flow cytometry at 0, 30, and 90 days post-RAIT. Both the percentage and absolute number of circulating regulatory T cells were significantly lower in the postoperative DTC compared to the healthy controls. Notably, the absolute number of multiple lymphocyte subgroups significantly decreased at 30 days post-RAIT compared to those pre-RAIT. The absolute counts of these lymphocytes were recovered at 90 days post-RAIT, but not at pre-RAIT levels. Additionally, the Th17 cell percentage before RAIT was positively correlated with thyroglobulin (Tg) levels after RAIT. The tumor burden might contribute to increased levels of circulating Tregs. In conclusion, RAIT caused transient radiation damage in patients with DTC and the percentage of Th17 cells before RAIT could be a significant predictor of poor prognosis in patients with DTC.